Wychowanie do podmiotowości - podmiotowość etyczna = Education to Subjectivity - Ethical Subjectivity - Wiatrowska, Leokadia (Zielona Góra: Uniwersytet Zielonogórski, Wydział Pedagogiki, Psychologii i Socjologii)
Education in its definition has many aspects and contexts, but it is impossible to question its axiological dimension. Through the pursuit of the value, in the course of educational acts and autonomous choices of the subject being raised, ethical education is realized and, in turn, it is the basis of the ethical subjectivity.
Keywords: dziecko; przedszkole; wychowanie etyczne; rozwój etyczny; podmiotowość etyczna; child; kindergarten; ethical education; ethical development; ethical subjectivity